(untitled) (Western Pacific Surveillance and Response, 2015)
OBJECTIVE: To assess the public health risk posed by the ongoing Ebola Virus Disease (EVD) epidemic in West Africa to the people of the Pacific island countries and areas (PICs). METHOD: The likelihood of EVD spread and the magnitude of public health impact in the PICs were assessed to clarify overall risk. Literature about the hazard, epidemiology, exposure and contextual factors associated with EVD was collected and reviewed. Epidemiological information from the current EVD outbreak was assessed. RESULTS: As of 14 January 2015, there have been at least 21 296 reported cases of EVD, with at least 8 429 deaths.(1) The outbreak has been contained in six West African countries with only a small number (n=6) of cases (all with epidemiological links to the outbreak in West Africa) detected in non-West African countries. PICs’ geographic isolation from the outbreak and lack of travel or trade links between countries with intensive transmission and the Pacific means that EVD importation is very unlikely although it has the potential to occur. The health and non-health consequences, should a case be imported, would be major EVD preparedness planning in the Pacific islands aims to reduce the health and socioeconomic consequences of a travel-related case of EVD arriving in a PIC, and the adverse impact on the health system responding to a case. DISCUSSION: The risk assessment’s findings highlight the need to enhance preparedness for Ebola virus disease in the Pacific. Ebola preparedness should focus on strengthening the capacities outlined in the WHO Framework for Action on Ebola. Key to this is ensuring ability to: detect and respond to suspected EVD cases quickly; isolate and manage cases in appropriate facilities; and prevent further infections through meticulous application of infection prevention and control practice. Efforts to prepare for Ebola should enhance more broadly all-hazards public health preparedness in line with International Health Regulations’ objectives.